Makna Cover Majalah Tempo “Siasat Pinokio Senayan” Edisi 19-25 Oktober 2020 (Analisis Semiotika Charles Sanders Pierce) - Sinta Rosiani; Indrawati; Jufrizal (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research is entitled "The Meaning of Tempo Magazine Cover "Siasat Pinokio Senayan" October 19-25, 2020 Edition (Charles Sanders Pierce Semiotics Analysis)". Mass media is one of the places to disseminate the latest information and news to the public which is formed due to the process of sending information from one person to another. The number of media that have sprung up, journalists are faced with intense competition to present information that attracts the attention of the public including print media such as magazines that contain stories, pictures, tips and tricks. In this study, to analyze the research approach or method used is a qualitative research method that explains descriptively the meaning of the cover in tempo magazine. In this study, the subject under study is the cover of the October 17-25, 2020 edition of Tempo Magazine with the title "Siasat Pinokio Senayan". This edition raises news about the issue of the Indonesian Parliament which has passed the Omnimbus Law on Job Creation Bill into law. The ratification of the law is considered hasty and polemical both in terms of content and the ratification process. The data used as a reference in this research comes from library materials such as books, documents, and other materials that can be a reference for researchers. The literature is used to support the semiotic analysis of the cover of the October 17-25, 2020 edition of "Siasat Pinokio Senayan" magazine. The types of data sources include literature on semiotics, journal articles related to semiotics and the analysis of signs, relevant Tempo magazine documents, as well as references from libraries, archives and online sources. Semiotics is the approach used to analyze the data, focusing on the use of signs as a tool in exploring the reality of human life. The main concepts in semiotics involve symbols and signs. The first basic concept in semiotics is the sign, which is considered as a trigger and interpreted as a sign of another situation. This can be seen from the technique of making the cover and the classification of icons and objects on the cover which gives a special impression to the readers.